2020
DOI: 10.1111/ajag.12890
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Toolkit to support sustainable culture change in residential aged care

Abstract: Objective This study aimed to develop and evaluate a Toolkit to support implementation of the Towards Organisational Culture Change (TOrCCh) intervention, with minimal external facilitation, in aged care facilities, to implement long‐lasting organisational change. Methods Eight residential aged care facilities across two Australian states participated. A Toolkit was drafted iteratively, engaging staff from participating sites and a reference group. Participating facilities undertook two change projects utilisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…One notable term is the safety attitude questionnaire and survey, which focuses on the application of validated scales to obtain accurate information about the attitudes and behaviors of organization members. For example, a survey conducted among pharmacy personnel in Saudi Arabia revealed that the organizational culture fell below the standard [81]. This highlights the significance of assessing and addressing organizational culture for ensuring safety and improving performance.…”
Section: Citations Per Authormentioning
confidence: 99%
“…One notable term is the safety attitude questionnaire and survey, which focuses on the application of validated scales to obtain accurate information about the attitudes and behaviors of organization members. For example, a survey conducted among pharmacy personnel in Saudi Arabia revealed that the organizational culture fell below the standard [81]. This highlights the significance of assessing and addressing organizational culture for ensuring safety and improving performance.…”
Section: Citations Per Authormentioning
confidence: 99%